ANALISIS LAYANAN WEBSITE PERPUSTAKAAN SUMATERA SELATAN DALAM MENINGKATKAN KEPUASAN PENGGUNA - Masroni Dedi Kiswanto; Terttiaavini Terttiaavini; Ahmad Sanmorino (Jurnal Ilmiah Matrik, 2017)
The purpose of this study is to analyze the factors that affect user satisfaction on the website library South Sumatra using webqual 4.0 method. Data collection in this research is done by spreading kuisioner to 40 respondent. The result of correlation test in research shows that the quality of usage and quality of information have a positive relationship while the quality of interaction has a negative relationship with user satisfaction. When viewed based on t test shows that the variable quality of usage and quality of information have a positive effect on user satisfaction library website south sumatera. While the quality of interaction variables do not have a positive effect on user satisfaction library website of South Sumatera, thus the quality of library service website of South Sumatera needs to be increased in order to increase user satisfaction.